Drug-Induced Liver Injury Associated with the Use of Everolimus in a Liver Transplant Patient - Serena Patel; Michel H. Mendler; Mark A. Valasek; Shirley M. Tsunoda (Case Reports in Transplantation)
Drug-induced liver injury (DILI) has not been previously reported as a complication of treatment with everolimus. A 56-year-old Caucasian male liver transplant recipient developed DILI after receiving everolimus. Elevations in transaminase levels occurred within a week of starting everolimus and an upward trend in the transaminase levels continued with supporting histopathologic changes confirmed by liver biopsy. Within one week of drug discontinuation, his liver enzymes normalized to baseline. This report includes a brief review of the pharmacokinetic properties of everolimus, a review of the relevant literature, and an analysis using the RUCAM and Naranjo algorithms.